ROLE OF FLOATING PHOTOVOLTAIC (FPV) DEVELOPMENT IN ENHANCING THE RENEWABLE ENERGY-BASED MSME ECONOMY IN LAKE KHAYANGAN, PEKANBARU - Ardiansyah Putra; Muhammad Yunus; Zulkarnain Umar (Integrative Perspectives of Social and Science Journal, 2025)
The deployment of Floating Photovoltaic (FPV) in Lake Khayangan, Rumbai, Pekanbaru, represents a strategic solution to reduce dependency on fossil fuels and foster an economy based on renewable energy (RE). This study discusses the contribution of FPV to enhancing the capacity of Micro, Small, and Medium Enterprises (MSMEs) by providing clean, affordable, and sustainable energy. Using qualitative analysis and a statute approach, the research identifies opportunities and challenges in developing FPV at Lake Khayangan and its impact on the local economy. The results reveal that FPV can reduce MSMEs' operational costs, create new employment opportunities, and increase local community income. The study also examines effective policies and strategies for FPV establishment to support MSME economic growth. Recommendations for the government, developers, and MSMEs are provided to optimize the potential of FPV at Lake Khayangan. These findings can serve as a foundation for developing a sustainable, renewable-energy-based community economy and improving the quality of life of people around Lake Khayangan. This research contributes to local and national economic development and supports Indonesia’s renewable energy policies.